Falsas Apariencias - Lynn, Jonathan; Perry, Matthew; willis, Bruce (Barcelona Manga Films, 1999)
Nick is a struggling dentist in Canada. A new neighbor moves in, and he discovers that it is Jimmy "The Tulip" Teduski. His wife convinces him to go to Chicago and inform the mob boss who wants Jimmy dead.
Bruce Willis, Matthew Perry, Rosanna Arquette
Estados Unidos, 1999
No recomendada para menores de 13 años
Idiomas: V.O. inglés, castellano. Subtítulos en castellano
Keywords: Películas cinematográficas -- DVD